Effect of β-sitosterol on the expression of HPV E6 and p53 in cervical carcinoma cells - Cheng, Dali; Guo, Zhiqiang; Zhang, Shulan (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : In the absence of effective therapeutic strategies, cervical carcinoma continues to be second on the list of mortality rates of malignant tumours found in women. We investigated the effects of β-sitosterol, a natural product isolated from traditional Chinese herbs, on Caski and HeLa cervical carcinoma cells. Material and methods : Morphological changes were examined by light microscopy. Ultrastructures of Caski and HeLa cells treated with 20 µmol/l β-sitosterol were documented by scanning electron microscopy and transmission electron microscopy. Changes in mRNA and protein expression were quantified respectively using Real-Time qPCR and western blot methods. Results : Treatment of Caski and HeLa cells with β-sitosterol resulted in reduced expression of PCNA, indicative of an inhibitory effect on cell proliferation. This was associated with increased p53 mRNA levels and decreased amounts of HPV E6 transcripts. Expression of p53 and HPV E6 proteins followed a similar trend as that observed for the corresponding transcripts. Caski and HeLa cells treated with β-sitosterol exhibited loss of cell surface microvilli, increased electron density of cell membrane, and decreased organelles. Conclusions : In conclusion, treatment of Caski and HeLa cells with β-sitosterol significantly suppressed the expression of genes involved in cell proliferation and oncogenic transformation, while augmenting the expression of genes involved in apoptosis and tumour suppression. Ultrastuctural characterisation of Caski and HeLa cells treated with β-sitosterol further confirmed the anti-proliferative and anti-cancer activity of this natural product isolated from traditional Chinese herbs.